Use of gamification, the game to improve skills in learners - Camacho Parra, María Luz
This article aims to show the experience of the use of elements and design of the games in the Systems Technician competences, focused on the apprentices of the 1621530 tab in a non-playful context. The experiences discussed here aim to give an approach to the use of new pedagogical, didactic strategies where the apprentice’s taste for games is taken into account, teaching happens in a playful way and the instructor feels satisfaction for the achievement of meaningful learning when using real and productive contexts.